Paraffin Sebagai Material Penyimpan Kalor Laten - Agus Dwi Korawan (SIMETRIS, 2019)
Paraffin is a material that is easily obtained because it is sold in supermarkets, in addition to household needs, paraffin can be used as a thermal storage material, this is because paraffin has many good properties. To find out the properties needed as heat storage material, a DSC test was performed. Based on the test results and analysis, the results show values that are almost the same as the existing references.